(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Flanders system attempts to categories all the verbalbehaviour to be found in the classroom. It has two main categories or group:teacher talk and pupil talk. A third category covers other verbal behaviouri.e. silence or confusion.